Supercapacitor electrodes based on Ru/RuO2 decorated on N,S-doped few-layer graphene - Kumar M.; Kar K.K.; Paik P. (My University, 2025)
Innovatively designed flexible and high-performance shape memory polymer supercapacitors are promising next-generation energy storage devices for portable and wearable electronics. Therefore, thermally induced smart shape memory polymer polyurethane was synthesized using polycaprolactone/poly(ethylene glycol)/hexamethylene diisocyanate (PCL/PEG/HDI) in which the incorporation of PEG successfully assisted in lowering the transition temperature. The resulting polymer exhibits a remarkable transition temperature of 50 °C and a shape recovery ratio of 100 % at a strain of 300 %. The smart polymer was coated with a silver paste to ease the electron flow followed by coating with the electrode. Hybrid electrode materials are prepared in two stages. Initially, a few layers of holey-graphene were synthesized, where BET surface area reveals the presence of pores that are tuned by isothermal treatments in O2-atmosphere. Subsequently, active hybrid electrode materials nanostructured Ru/RuO2 decorated N, S-doped few layers of holey graphene were synthesized using hydrothermal methods. Here, nitrogen and sulfur doping in the basal or edge plane served as catalysts and metal coordination sites, facilitating the uniform distribution of ruthenium nanoparticles on the graphene. It is further confirmed by the density function theory (DFT) calculation using the adsorption energy. The optimized hybrid electrode material demonstrates a specific capacitance of 1297 mFcm−2 at a current density of 2 mAcm−2. A flexible-shape memory polymer supercapacitor exhibits a notable device-specific capacitance of 189 mFcm−2 at a current density of 1 mAcm−2, a high energy density of 45 µWhcm−2 at a power density of 0.25 mWcm−2, with 81 % of specific capacitance retention after eight shape programming and recovery cycle. Excellent shape recoverability and robust electrochemical performance make the as-fabricated symmetric supercapacitors a promising candidate for integration in flexible electronic applications. © 2024 Elsevier B.V.